Rapid Flow Cytometry Detection of a Single Viable Escherichia coli O157:H7 Cell in Raw Spinach Using a Simplified Sample Preparation Technique - Williams, Anna J.; Cooper, Willie M.; Ramsaroop, Shawn; Alusta, Pierre; Buzatu, Dan A.; Wilkes, Jon G. (Frontiers in Microbiology, 2017)
Very low cell count detection of Escherichia coli O157:H7 in foods is critical, since an infective dose for this pathogen may be only 10 cells, and fewer still for vulnerable populations. A flow cytometer is able to detect and count individual cells of a target bacterium, in this case E. coli O157:H7. The challenge is to find the single cell in a complex matrix like raw spinach. To find that cell requires growing it as quickly as possible to a number sufficiently in excess of matrix background that identification is certain. The experimental design for this work was that of a Food and Drug Administration (FDA) In-House Level 3 validation executed in the technology’s originating laboratory. Using non-selective enrichment broth, 6.5 hours incubation at 42 ◦C, centrifugation for target cell concentration, and a highly selective E. coli O157 fluorescent antibody tag, the cytometry method proved more sensitive than a reference regulatory method (p=0.01) for detecting a single target cell, one E. coli O157:H7 cell, in 25 g of spinach. It counted that cell’s daughters with at least 38× signal-to-noise ratio, analyzing 25 samples in total-time-to-results of 9 h.